Types of destructive attitude of parents to the child's and adolescent's sports activity - Khvatskaya E.E. ,; Latysheva N.E. ,; Andreev Vl.V. ,; Andreev Vit.Vl. ,; Stanislavskaya I.G. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determining the trend of changes in the severity of the types of destructive attitudes of parents towards the child and teenager’s sports activities in order to clarify the constructive model of their behavior in the structure of psychological support for the sports reserve. Methods and structure of the study. The main toolkit is «Methodology for studying parents attitudes towards their child’s sports activities» by E.E. Khvatskaya, N.E. Latysheva. Parents of young athletes took part in the study (2018 – n=56, 2019 – n=176, 2022 – n=87). The participation format is anonymous. To assess the significance of differences, Fishers test was used. Results and conclusions. The severity of the destructive attitude of parents towards the child and teenagers sports activities as a source of excessive/inappropriate difficulties for the latter revealed a tendency for the number of parents with an established «model» of behavior to increase (2018 – 46,4%; 2019 – 45,45%; 2022 – 46%), more often compensating. The situational «model» in 2022 is more typical for the negative type of attitude of parents towards their child and teenagers sports activities. At the trend level, the number of parents without a certain model of behavior (type of attitude) decreased by 8,7% (according to the φ* criterion - Fishers angular transformation: φ*amp = 1,321 p>0,05). A constructive «model» of parental behavior has been identified, aimed at creating and maintaining a healthy sports environment. The number of parents with a destructive attitude towards their childs and teenagers sports activities, especially with an established «model» of behavior (often compensatory type, then negative and indifferent), is quite stable (according to data from 2018, 2019 and 2022). There was a decrease at the trend level in the number of parents with an uncertain «model» of behavior, and its increase with the situational manifestation of a negative attitude (one of the significant adults). A constructive «model» of parental attitudes and behavior in the context of a healthy sports environment is presented.